The Impact of Na and K on Properties of Cu2ZnSnS4 Thin Films Prepared by Ultrasonic Spray Technique. Issue 10 (24th October 2017) - Sekkati, Mouaad; Taibi, Mhamed; Schmerber, Guy; Benamar, El Bachir; Regragui, Mohammed; Cherkaoui El Moursli, Fouzia; Leuvrey, Cedric; Edfouf, Zineb; Sekkat, Zouheir; Dinia, Aziz; Slaoui, Abdelilah; Abd‐Lefdil, Mohammed
Abstract : CZTS thin films are deposited onto glass and Mo‐coated glass substrates by ultrasonic spray technique, followed by a sulfurization under argon atmosphere at 500 °C during 1 h. We have investigated how the addition of the alkali can influence Cu2 ZnSnS4 thin films properties. X‐ray diffraction and Raman spectroscopy proved that CZTS has the kesterite structure with a preferential orientation along 112. The values of Cu/(Zn+Sn) and (Zn/Sn) ratios, determined by energy dispersive spectroscopy, for undoped CZTS and alkali‐doped CZTS are observed to be affected by the alkali doping. The electrical resistivity, for CZTS films deposited on glass substrates, decreased after alkali doping from 9.2 10 −1 Ω · cm for undoped CZTS to reach 1.8 10 −1 and 4.2 10 −1 Ω · cm for 15% content of Na and K, respectively. Abstract : We use spray chemical easy route to elaborate potassium doped Cu2 ZnSnS4 (CZTS) thin films. The films present the kesterite structure. We obtain the best values of <112> preferential orientation coefficient and the large grain size for CZTS:K (5%) films.